Análise do comportamento de prismas grauteados de alvenaria estrutural cerâmica - Grohmann, Leandro Zampieri (2006)
The main purpose of this thesis is to evaluate the behavior of clay prisms grouted, partially grouted and ungrouted under compression loads in order to analyze the influence and performance of the grout, as well as to seek how to optimize its applicability. For that, testing was done with different grouts and grouting ratios. The testing was done in 120 prisms under simple axial compression load, where sets of prisms had two different types of mortar (A1 and A2), three different grouts (G1, G2 e G3) and four different ratios of grouted cavities (0%, 33%, 66% e 100%). For this testing, all the materials and components were previously characterized. Based on experimental data, the analysis of the results was done taking into account the different sets of prisms grouping them according to their mortar, grout and grouting ratio. The variance analysis for the sample was done in order to prove the existence of significant differences among the various group combinations. It was also performed a comparison among the data found and results gathered by other researchers. Another investigation was done regarding the fracture behavior of prisms and the influence of interactions among block, mortar and grout was observed. Through the analysis of the results, some of the conclusions regarding the behavior of prisms were: the importance of the mortar s strength for the compression strength of the prisms; the increase in the strength of the grout does not indicate a significant increase in the prisms strength; the significant increase in the prisms strength is noticed only when the totality of the prisms cavities are grouted. Overall, the use of masonry walls with partially grouted cavities is efficient if properly used. For that, the types of grout and mortar must be suitable to and in accordance with the mechanical behavior of the blocks used.